2002
DOI: 10.1191/1464993402ps043ra
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of long-term growth in India: a Keynesian approach

Abstract: This paper attempts an eclectic synthesis on long-term growth, which integrates two standard models -the neoclassical model with the endogenous growth and export-led model of growth. A vector autoregressive (VAR) model has been used for India from 1950 to 1995 using Johansen's multivariate cointegration approach to derive latent equilibrium relationships, and the short-run error correction equations are then estimated. Two cointegrating relationships for real output and real private investment, respectively, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…1 = 2 . However, if private investment is more efficient and productive than public sector investment, then the estimated coefficient on private investment would be larger than the public investment coefficient, such that 1 > 2 , [9], [10], [12], [38] in particular, emphasise that the importance of the relative size of 1 and 2 , as there remains some uncertainty about whether public sector investment encourages or depresses private investment.…”
Section: Theoretical Framework and Model Specificationmentioning
confidence: 99%
“…1 = 2 . However, if private investment is more efficient and productive than public sector investment, then the estimated coefficient on private investment would be larger than the public investment coefficient, such that 1 > 2 , [9], [10], [12], [38] in particular, emphasise that the importance of the relative size of 1 and 2 , as there remains some uncertainty about whether public sector investment encourages or depresses private investment.…”
Section: Theoretical Framework and Model Specificationmentioning
confidence: 99%
“…Furthermore, Mallick (2002) investigated influences of factors on economic growth in India from 1950 to 1995 using a VAR model. The study found that economic output depends upon private investment, human capital, real interest rate, and public investment.…”
Section: Empirical Literaturementioning
confidence: 99%
“…If the government borrows during full-employment equilibrium, it would result in displacement of resources from the private sector for use in the public sector. Given the resources/funds availability in the economy and the private sector demand for the same capital, an increase in government demand for these funds increases the interest rate, which in turn leads to the crowding-out of private investment and setting off recessionary trends (Mallick, 2002). However, the overall impact if interest rate on aggregate investment ceteris paribus (as investment depends on other factors as marginal efficiency of investment and cost of capital depends on the elasticity of investment demand with regard to interest rates.…”
Section: Theoretical Reviewmentioning
confidence: 99%
“…This requirement for an unbalanced budget has been extended by theories in public finance to provide a framework through which a country could borrow to finance development programs in the public sector in order to revive economic prosperity. It should therefore be understood that flexible budgeting is just an extension of classical/orthodoxy theory and its created to accommodate government borrowing as an instrument of fiscal policy (Mallick, 2002).…”
Section: Theoretical Reviewmentioning
confidence: 99%